Comparison of plant feedstocks and methods to recover leaf proteins from wet fractionation of alfalfa for potential use in aquaculture, poultry, and livestock feeds. Issue 2 (15th June 2021) - Coburn, Jessica; Wells, M. Scott; Sheaffer, Craig C.; Ruan, Roger; Samac, Deborah A.
Abstract: Alternative plant‐based protein sources are needed for supplementing or replacing fishmeal in formulated animal feeds. Alfalfa ( Medicago sativa L.), a perennial legume, is grown worldwide as a high‐protein forage crop used primarily for dairy and beef cattle feeds. However, its utility as a protein source for feeding other farmed animals has great potential. Wet fractionation can provide several products that increase the value of the crop. The amount of alfalfa protein concentrate (APC) recovered from a fresh press filtrate was measured from several feedstocks: herbage of a nonlodging biomass‐type alfalfa, genetically modified reduced‐lignin alfalfa, and conventional alfalfa as well as from leaves of the biomass type fractionated at harvest. Additionally, five methods for APC recovery were compared. Approximately 854 kg of APC, 7, 109 kg of press residue suitable as low quality animal feed, and 4.5 Tg of dry hay could be produced annually from a hectare of biomass‐type alfalfa. The amounts of APC recovered from a reduced‐lignin alfalfa and a conventional cultivar were similar. Acid‐based precipitation methods resulted in the largest recovery of APC, whereas heating produced the highest concentration of protein in the concentrate and highest concentration of methionine, lysine, and threonine. The percentage of fatty acids and sugars in the concentrate varied significantly by precipitation method. All methods resulted in low amounts of fiber in the concentrate. Our results indicate that a nonlodging biomass‐type alfalfa can produce high yields of APC and co‐products with fewer harvests than a conventional cultivar, which reduces costs and promotes crop productivity. Core Ideas: Herbage from nonlodging alfalfa produced an estimated 854 kg protein concentrate per hectare. Field separated leaves produced an estimated 524 kg protein concentrate per hectare. Protein concentrate yields were similar for reduced‐lignin and conventional cultivars. Heat treatment of the press filtrate resulted in the highest crude protein concentration.